The Impact of Green Accounting, Environmental Performance, and Capital Structure on the Financial Performance of Consumer Goods Companies in Indonesia - Ratna Sari, Sri; Fadillah, Arum Nur; Supira, Wita; Wulandari, Sekar Asri Pebri; Kustina, Lisa (Growth: Journal Management and Business, 2025)
Environmental issues and corporate sustainability have become strategic concerns, especially in the manufacturing sector, which is often associated with high environmental risk and resource consumption. However, previous studies have shown inconsistent results regarding the relationship between environmental initiatives and financial outcomes. The uncertainty of the significant relationship between green accounting and environmental performance on financial performance, which in previous studies showed varying research results. This study aims to examine the Effect of Green Accounting Implementation, Environmental Performance, and Capital Structure on Financial Performance in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Green accounting is also called a type of accounting that takes into account environmental impacts so that it involves aspects of environmental management costs in a company's financial statements to increase transparency and accountability. In addition, environmental performance is assessed through the Company Performance Rating Program in Environmental Management (PROPER), while the capital structure describes the proportion between the company's debt and equity. This study uses a quantitative method with panel data regression analysis. The results of the study suggest that Green Accounting and Environmental Performance do not have a significant effect on the company's financial performance, while the capital structure has a significant effect. The results of this study explain that companies need to balance environmental availability and financial management to increase competitiveness. This study contributes to the related literature by providing empirical insights from the Indonesian consumer goods sector and emphasizes the need for aligning sustainability strategies with financial planning.